THE IMPORTANCE OF ARTICULATION EXERCISES IN SPEECH THERAPY - Islam Shavkatovich Tilovbayev; Azizbek Jakhshimuratovich Tajimuratov (Journals Park Publishing, 2023)
This article discusses the importance of articulation exercises for children who have speech impediments and highlights the factors that contribute to it.
Keywords: include dislalia, articulation gymnastics, sweet jam, thyme, and currants.